Defeating lethal cancer: Interrupting the ecologic and evolutionary basis of death from malignancy - Kenneth J. Pienta; Patrick L. Goodin; Sarah R. Amend (CA: A Cancer Journal for Clinicians, 2025)
Abstract Despite the advances in cancer prevention, early detection, and treatments, all of which have led to improved cancer survival, globally, there is an increased incidence in cancer‐related deaths. Although each patient and each tumor is wholly unique, the tipping point to incurable disease is common across all patients: the dual capacity for cancers to metastasize and resist systemic treatment. The discovery of genetic mutations and epigenetic variation that emerges during cancer progression highlights that evolutionary and ecology principles can be used to understand how cancer evolves to a lethal phenotype. By applying such an eco‐evolutionary framework, the authors reinterpret our understanding of the metastatic process as one of an ecologic invasion and define the eco‐evolutionary paths of evolving therapy resistance. With this understanding, the authors draw from successful strategies optimized in evolutionary ecology to define strategic interventions with the goal of altering the evolutionary trajectory of lethal cancer. Ultimately, studying, understanding, and treating cancer using evolutionary ecology principles provides an opportunity to improve the lives of patients with cancer.